Aktualisasi Dakwah Dai Millennial di Ruang Maya: Perspektif Etika Dakwah dengan Studi Kasus di Kota Medan - Nashrillah MG (Islam Futura, 2018)
This article presents the actualization of the preaching of millennial dai(preacher) group in cyberspace. The millennial da'i group is a young preacher who grows and develops together with advances in information technology, thus this group highly "dependent" on information technology. To understand the actualization of the millennial dai in cyberspace, several questions about the identity of the millennial da'i and the actualization of preaching in cyberspace were asked. This study found that the identity of the millennial was formed based on high "dependence" on social media, had a higher education level, and was actively involved in religious organizations. Whereas the actualization in cyberspace, especially social media like Facebook is done by self-actualization and actualization of preaching. Self-actualization follows the general developments on Facebook, such as selfies and narcissism and these become a common practice of millennial da'i. The actualization of preaching shows the shifting of preaching from something "sacred" to something profane, as well as there is an effort to use Facebook as a support factor of certain groups. Various expressions presented by millennial dai in cyberspace explain that the ethics of preaching or da'wah does not become a reference in the activities of preaching which has led it to experience disorientation from religious interests into economic interests.